2022
DOI: 10.5812/jjm.120801
|View full text |Cite
|
Sign up to set email alerts
|

Changing Trends of Candida Species and Antifungal Susceptibility Profile of Candida Bloodstream Isolates: A 5-Year Retrospective Survey

Abstract: Background: Candida species have emerged as one of the most common causes of bloodstream infections (BSIs). There are limited data on the distribution of Candida spp. and susceptibility by year. Objectives: In this study, we analyzed changes in the distribution of Candida spp. and their antifungal susceptibility profiles from blood cultures. Methods: Records from January 2016 to December 2020 were obtained from the microbiology laboratory in Istanbul. Antifungal susceptibility tests were performed using the VI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
1
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 41 publications
2
1
1
Order By: Relevance
“…Our data revealed that the majority of isolates (> 70%) were biofilm producers and positive for biofilm related genes (HWP1 and ALS1 ). In agreement, Brunetti et al 23 stated that 69.28% of Candida BSIs were biofilm producers with the highest intrinsic production among C . albicans and C .…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…Our data revealed that the majority of isolates (> 70%) were biofilm producers and positive for biofilm related genes (HWP1 and ALS1 ). In agreement, Brunetti et al 23 stated that 69.28% of Candida BSIs were biofilm producers with the highest intrinsic production among C . albicans and C .…”
Section: Discussionsupporting
confidence: 66%
“…Fluconazole Our data revealed that the majority of isolates (> 70%) were biofilm producers and positive for biofilm related genes (HWP1 and ALS1). In agreement, Brunetti et al 23 stated that 69.28% of Candida BSIs were biofilm producers with the highest intrinsic production among C. albicans and C. tropicalis. Additionally, Treviño-Rangel et al 28 discovered that all the strains (89 isolates) produced biofilm with the highest biofilm density among C. tropicalis.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…In contrast to our study, few studies reported C. albicans as the predominant pathogen (39.42%), followed by C. parapsilosis (34.02%). 18 The distribution of the species are different in various regions and studies. For management of patients, determination of changes in the distribution of candida species is important Pulmonary aspergillosis (71.9%) was most common manifestation among all the cases of aspergillosis, followed by sino-nasal aspergillosis (18.8%), cutaneous aspergillosis (7.8%) and ocular aspergillosis (1.6%).…”
Section: Discussionmentioning
confidence: 99%